2014
DOI: 10.1186/1471-2202-15-74
|View full text |Cite
|
Sign up to set email alerts
|

Hirano bodies differentially modulate cell death induced by tau and the amyloid precursor protein intracellular domain

Abstract: BackgroundHirano bodies are actin-rich paracrystalline inclusions found in brains of patients with Alzheimer’s disease (AD), frontotemporal dementia (FTD), and in normal aged individuals. Although studies of post-mortem brain tissue provide clues of etiology, the physiological function of Hirano bodies remains unknown. A cell culture model was utilized to study the interactions of mutant tau proteins, model Hirano bodies, and GSK3β in human astrocytoma cells.ResultsMost tau variants showed co-localization with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 113 publications
(147 reference statements)
0
14
1
Order By: Relevance
“…We also found increased expression of pho-TAU in the hippocampus in all cases. Although it has been suggested that increased TAU expression is linked to AICD production (63), we found no correlation between the two. It is therefore most likely due to increased intraneuronal Aβ expression.…”
Section: Discussioncontrasting
confidence: 99%
“…We also found increased expression of pho-TAU in the hippocampus in all cases. Although it has been suggested that increased TAU expression is linked to AICD production (63), we found no correlation between the two. It is therefore most likely due to increased intraneuronal Aβ expression.…”
Section: Discussioncontrasting
confidence: 99%
“…Model Hirano bodies have been induced in Dictyostelium , mammalian cultured cells, and a range of complex physiological effects have been reported ( Davis et al, 2008 ; Furgerson et al, 2012 ; Ha et al, 2011a ; Maselli et al, 2002 , 2003 ; Spears et al, 2014 ). These results led to the effort to identify the proteins in these inclusions.…”
Section: Discussionmentioning
confidence: 99%
“…These altered forms exhibit gain-of-function activated F-actin binding ( Griffin et al, 2014 ; Maselli et al, 2002 , 2003 ). Proteins present in Hirano bodies in postmortem tissues were also found in model Hirano bodies ( Davis et al, 2008 ; Furgerson et al, 2012 ; Ha et al, 2011a ; Maselli et al, 2002 , 2003 ; Spears et al, 2014 ). These results prompted further investigation of some proteins found in brain specimens utilizing modern reagents in live cells expressing model Hirano bodies and have shed light on the possible physiological role(s) of Hirano bodies in neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…8 The latter are actin-rich inclusions that seem to be associated with tau, the main component of neurofibrillar y tangles. 11,12 In the second patient, Aβ40 fibres were periodically twisted and varied in width. 8 'The predominant structures … are clearly different', the authors comment, adding that 'the structural specificity of brain-seeded Aβ40 fibrils … is remarkable'.…”
Section: Molecular Origamimentioning
confidence: 99%